2007
DOI: 10.1016/j.jtcvs.2006.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux in patients with idiopathic pulmonary fibrosis referred for lung transplantation

Abstract: A majority of patients with idiopathic pulmonary fibrosis have pathologic reflux. Symptoms do not distinguish between those with and without reflux. In these patients, reflux is associated with a hypotensive lower esophageal sphincter and abnormal esophageal peristalsis, and often extends into the proximal esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 20 publications
(26 reference statements)
6
101
1
8
Order By: Relevance
“…Recent studies of patients with idiopathic pulmonary fibrosis and who were lung transplant candidates have shown that reflux is related to both alterations. (23) This dual manometric alteration might be related to the severity of the pulmonary profile, which is much greater in this type of terminal pulmonary disease patient than in those included in other studies. (20,22) In this regard, the failure of two of the principal mechanisms of the antireflux barrier (LES and peristalsis), allowing the ascension of the refluxed material and its permanence in the esophagus for a long time, can, together, contribute results were abnormal in 44%, including 50 (35.2%) of the asthma patients who presented no digestive symptoms.…”
Section: Resultsmentioning
confidence: 68%
“…Recent studies of patients with idiopathic pulmonary fibrosis and who were lung transplant candidates have shown that reflux is related to both alterations. (23) This dual manometric alteration might be related to the severity of the pulmonary profile, which is much greater in this type of terminal pulmonary disease patient than in those included in other studies. (20,22) In this regard, the failure of two of the principal mechanisms of the antireflux barrier (LES and peristalsis), allowing the ascension of the refluxed material and its permanence in the esophagus for a long time, can, together, contribute results were abnormal in 44%, including 50 (35.2%) of the asthma patients who presented no digestive symptoms.…”
Section: Resultsmentioning
confidence: 68%
“…However in non IPF patients, they didn't find any significant correlation between the severity of GER and the degree of lung fibrosis, which indicated that more damage and excessive fibrosis occurred in IPF diagnosed patients having more severe GER. However, Sweet et al [7] illustrated that 25-65% was the range of the GER symptoms in their patients. They detected that the specificity of the presence of actual GER pathology was 71% for their patients.…”
Section: Resultsmentioning
confidence: 86%
“…In many researches, it was detected that heartburn, regurgitation and dysphagia as common symptoms of GER aren't detected in many IPF patients. So, screening of abnormal GER in IPF patients by using the symptoms only is not appropriate method [7]. There is no accurate diagnostic testing for microaspiration and GER as declared by many researches.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to scleroderma, patients with IPF have a high prevalence of GERD [12,65,[73][74][75], leading to the hypothesis that recurrent occult microaspiration may drive the ongoing inflammation characteristic of this disease. This should not be confused with acute exacerbation of IPF (progression of symptoms over weeks with radiographic airspace disease), as biopsies may also reveal organising pneumonia with underlying UIP in this syndrome [76,77].…”
Section: Ipfmentioning
confidence: 99%